A Bácska, a Drávaszög, a Muramellék (Muravidék) és a Muraköz újraegyesülése Magyarországgal : 1941. április-július - Botlik, József (Közép-Európai Közlemények, 2011)
In 1941 the state of Yugoslavia has fallen apart. It started on the 10th of April with Croatia declaring its independence –with this step Yougoslavia as a state has ceased. Armies of different countries –Germany, Italy, Hungary –marched to its territory. On the 11th of April Hungarian troops began to re-occupy the territory (Délvidék, Vajdaság) Hungary had lost in the treaty of Trianon. Hungarian people greeted the action with great enthusiasm. The study deals with the direct antecedents and the process of the re-occupation of Délvidék. It does not follow the marxist tradition of history, and exposes details that were not mentioned by the marxist historians, for example the Yugoslavian military attacks against Hungary before the 11th of April, 1941.